Monogamy, the Protective Fallacy: Sexual versus Emotional Exclusivity and the Implication for Sexual Health Risk. Issue 1 (2nd January 2016) - Swan, D. Joye; Thompson, Suzanne C.
Abstract : The authors examined the hypothesis that many individuals define monogamy based on emotional rather than sexual fidelity. Participants, 373 heterosexual college students and 282 gay men, read three vignettes of decreasing mitigation in which they imagined committing an act of infidelity against a hypothetical partner and where half the participants were cued to their emotional attachment toward the partner. Despite the infidelity, relationships in the emotional attachment–cued vignettes were rated as monogamous to a greater degree than relationships in the vignettes where emotional attachment was not cued. In addition, over one-third of the participants in our study reported infidelity in their current self-defined monogamous relationships yet also reported feeling more protected from sexual health risks and reported less condom use than individuals who defined their relationship as nonmonogamous. The implications for monogamy as a protective fallacy are discussed.